1999
DOI: 10.1074/jbc.274.21.14655
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Topography of the 100-kDa a Subunit (Vph1p) of the Yeast Vacuolar Proton-translocating ATPase

Abstract: The membrane topography of the yeast vacuolar proton-translocating ATPase a subunit (Vph1p) has been investigated using cysteine-scanning mutagenesis. A Cys-less form of Vph1p lacking the seven endogenous cysteines was constructed and shown to have 80% of wild type activity. Single cysteine residues were introduced at 13 sites within the Cys-less mutant, with 12 mutants showing greater than 70% of wild type activity. To evaluate their disposition with respect to the membrane, vacuoles were treated in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 50 publications
9
111
0
Order By: Relevance
“…The model of the a subunit presented here is in excellent agreement with these studies. First, the model agrees well with experiments that probed topology and accessibility of the a subunit by labeling residues mutated to cysteine to define them as luminal, membrane-embedded, cytoplasmic, or at the cytoplasmic border (31,38,39) (Fig. 4A).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The model of the a subunit presented here is in excellent agreement with these studies. First, the model agrees well with experiments that probed topology and accessibility of the a subunit by labeling residues mutated to cysteine to define them as luminal, membrane-embedded, cytoplasmic, or at the cytoplasmic border (31,38,39) (Fig. 4A).…”
Section: Resultssupporting
confidence: 72%
“…Other than these differences, comparison of the two states reveals only minor conformational changes in individual subunits, suggesting little flexibility in the enzyme as a whole (Movie S3). The T. thermophilus V/A-ATPase thus seems to be relatively rigid compared with the S. cerevisiae V-ATPase (8) Numerous studies, many by Forgac and coworkers, have investigated the topology, function, and subunit arrangement of the S. cerevisiae V-ATPase V O region (31,34,(38)(39)(40)(41)(42)(43)(44). The model of the a subunit presented here is in excellent agreement with these studies.…”
Section: Resultssupporting
confidence: 72%
“…In the earlier studies, [5][6][7][8] it was difficult to determine the orientation of the N-terminus of a-subunit isoforms, but it is now generally accepted that this domain is oriented toward the cytoplasm. Moreover, according to several recent electron microscopy studies of V-ATPases from different organisms 16,[38][39][40] and small-angle X-ray scattering data of NtpI 1-341 , 26 it was determined that the N-terminal domain of the a-subunit forms an elongated 1-shaped structure.…”
Section: Discussionmentioning
confidence: 99%
“…1 From a structural perspective, the topology of a-subunit is not understood. 4 For the yeast ''a'' subunit homolog Vph1, several topology models have been proposed over the years, [5][6][7][8] with the most recent model depicting eight transmembrane a-helices with both the Nterminal and C-terminal ends located on the cytoplasmic side of the membrane. 8 Although the location of the N-terminal region of the protein on the cytoplasmic site has been experimentally confirmed, its exact length has not been finally determined.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction with MBP in the dark followed by irradiation with ultraviolet light gave rise to a 135-kDa product that was recognized by the antibody against subunit E. The size of this complex is consistent with cross-linking of subunit E and subunit a of the V 0 domain. We have recently shown that subunit a contains a large soluble domain at the amino terminus, which is exposed on the cytoplasmic side of the membrane and is therefore situated to interact with the V 1 domain (35).…”
Section: Covalentmentioning
confidence: 99%